Social support following bereavement: The role of beliefs, expectations, and support intentions - Logan, E.; Thornton, J.; Kane, R.; Breen, Lauren (Routledge, 2017)
Social support is one of the strongest determinants of bereavement outcomes, yet little is understood about the community's recognition of grief and intentions to provide social support to grieving persons. Four-hundred and seventy-six adults responded to an online vignette and questionnaire measuring grief norms and supportive intentions. Respondent gender, age, and bereavement status all had some association with expectations of grief, intentions to support, perceived helpfulness of support attempts, and opinions towards the diagnostic classification of grief. Given that most bereavement support is informal, this study informs the development of community capacity to provide constructive, timely bereavement support.